Domestic violence in rural Uganda: evidence from a community-based study - Koenig Michael A.; Lutalo Tom; Zhao Feng; Nalugoda Fred; Wabwire-Mangen Fred; Kiwanuka Noah; Wagman Jennifer; Serwadda David; Wawer Maria; Gray Ron (The World Health Organization, 2003)
Although domestic violence is an increasing public health concern in developing countries, evidence from representative, community-based studies is limited. In a survey of 5109 women of reproductive age in the Rakai District of Uganda, 30% of women had experienced physical threats or physical abuse from their current partner - 20% during the year before the survey. Three of five women who reported recent physical threats or abuse reported three or more specific acts of violence during the preceding year, and just under a half reported injuries as a result. Analysis of risk factors highlights the pivotal roles of the male partner's alcohol consumption and his perceived human immunodeficiency virus (HIV) risk in increasing the risk of male against female domestic violence. Most respondents - 70% of men and 90% of women - viewed beating of the wife or female partner as justifiable in some circumstances, posing a central challenge to preventing violence in such settings.